1998
DOI: 10.1002/(sici)1098-2264(199804)21:4<333::aid-gcc7>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 18q predicts poor survival of patients with squamous cell carcinoma of the head and neck

Abstract: Tumor suppressor genes play an important role in normal growth regulation. Loss or inactivation of these genes has been implicated in the development of squamous cell cancer and progression of neoplasia. Previous studies in our laboratories have implicated chromosome 18 long‐arm deletions as a possible marker of progression in head and neck squamous cell cancer (HNSCC). To test this hypothesis, we evaluated DNA from 67 HNSCC patients for loss of heterozygosity (LOH) at 18q loci, and for association of LOH with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…5 Consistently with our findings, allelic loss on chromosome 8p have been associated with advanced tumor stages and poor survival 20 -22 similar to 11qter and 18q deletions. 10,23,24 However, our study also revealed further loci on several other chromosome arms.…”
Section: Discussionsupporting
confidence: 48%
“…5 Consistently with our findings, allelic loss on chromosome 8p have been associated with advanced tumor stages and poor survival 20 -22 similar to 11qter and 18q deletions. 10,23,24 However, our study also revealed further loci on several other chromosome arms.…”
Section: Discussionsupporting
confidence: 48%
“…7,38 -41 Lastly, this study failed to confirm our earlier findings that loss of heterozygosity at 18q was associated with poor survival. 42 Although recruitment for the previous work as well as the current inquiry both occurred at Henry Ford Hospital in Detroit, Michigan, there was no overlap in the 2 study populations. Differences in recruitment methods exist between the 2 studies.…”
Section: Discussionmentioning
confidence: 97%
“…TSG implicated in HNSCC carcinogenesis and located on chromosomes 8p and 18q remain to be identified. The presence of LOH on 18q is of particular interest since it was related to tumor stage and prognosis (Pearlstein et al, 1998). This correlation was also found in other types of tumors (i.e.…”
Section: Introductionmentioning
confidence: 86%